Mobile technology in a mathematics trail program: how does it works? - Cahyono, Adi Nur; Miftahudin, Miftahudin (Department of Mathematics, Universitas Negeri Semarang, 2018)
The aim of the study reported upon in this paper is to explore the potential of the use of mobile technology for supporting math trail program. An explorative study was conducted in the city of Semarang in Indonesia involving 30 students of SMPN 10 Semarang. The study consisted of an introduction session, a math trail activity supported by the use of mobile phone app, and a debriefing session. Data were gathered by means of participatory observation, students' work, and interviews. Findings indicate that math trail programs supported by the use of mobile phones have promoted the engagement of students in mathematical activities. The use of mobile technology has the potential to support the program. Mobile app has been able to play a role in guiding students in math trail activities with features offered, such as: navigation features, help buttons, and direct feedback.